Research on 5G Fronthaul Bearer Scheme under Co-construction and Sharing Mode - Guo-xin ZHANG; Ke-xin WEI; Xian-hu WEI (Guangtongxin yanjiu, 2022)
This paper briefly introduces the technical architecture of the 5th Generation Mobile Communication (5G) forward transmission network, analyzes the 5G forward transmission requirement under the 5G co-construction of China Telecom and China Unicom, and gives the implementation scheme of 5G forward transmission. Combined with the 5G co-construction engineering practices of China Telecom and China Unicom, the article gives 5G fronthaul network construction planning, engineering design and construction plan suggestions. Based on the passive wavelength division multiplexing technology, the operator can effectively reduce the consumption of optical fiber resources and reduce the cost of network construction, which provides guidance on how to achieve 5G fronthaul network coverage quickly and economically.